Predatory mites from crops and pastures in South Africa: potential natural enemies of redlegged earth mite Halotydeus destructor (Acari: Penthaleidae) - Halliday, R. B. (Zootaxa, 2005)
A survey was conducted in crops and pastures in the Western Cape Province of South Africa, in a search for predatory mites that could have potential for introduction into Australia as biological control agents of redlegged earth mite Halotydeus destructor (Penthaleidae). A total of over 1200 specimens was examined, and 56 species of predatory mites belonging to 14 families were found. Information is presented for 33 known species, including synonymy and bibliography, geographic distribution, and biology where known. Eight species in six families are described as new¨®Bdellodes edentata sp. nov. (Bdellidae), Hypoaspis calcarata sp. nov. (Laelapidae), Hypoaspis muellerae sp. nov. (Laelapidae), Macrocheles propinquus sp. nov. (Macrochelidae), Gamasiphoides lootsi sp. nov. (Ologamasidae), Gamasiphoides rykei sp. nov. (Ologamasidae), Pachylaelaps meganalis sp. nov. (Pachylaelapidae), and Rhagidia meyerae sp. nov. (Rhagidiidae). Fifteen species could not be fully identified because suitable specimens were not available. Of the 41 species that could be identified, nine are already present in Australia. A further 20 species are not known from Australia, but were rare in South Africa and therefore unlikely to be useful predators. Twelve species occurred in significant numbers in South Africa and are not known from Australia. Most of these are known or believed to be generalist predators, and are therefore unlikely to be approved for introduction into Australia. Chaussieria capensis (Anystidae) was considered to have potential and has been studied further. The survey did not identify any other species that were considered to be suitable as biological control agents.